An Unusual Case of Mullerian Choristomas in the Lumbar Region Presented as Spinal Dysraphism - Yaminy Pradeep Ingale; Arpana Dharwadkar; Sushama Gurwale; Charusheela Gore (Indian Spine Journal, 2025)
A choristoma is a benign growth of microscopically normal tissue that resembles a tumor and develops in an unusual place. Mullerian choristomas in connection with spinal dysraphism are incredibly uncommon; less than 10 cases have been reported in English literature. Here, we present a case of a 39-year-old female who has had lower back swelling since birth, along with difficulty in walking and lower-limb pain for 8 months. A computed tomography scan and magnetic resonance imaging of the spine show spinal dysraphism–spina bifida at L3–L4 level with lipomeningocele. An excisional biopsy of the swelling was done and sent for histopathology. A biopsy shows the presence of ectopic endometrial and fallopian tissue along with fibro-fatty tissue, which is confirmed by immunohistochemistry. Smooth muscles, stromal cells, and epithelium had positive estrogen receptors, according to immunohistochemistry. In addition, the stromal cells demonstrated a cluster of differentiation 10 positivity, indicating Mullerian derivation and the epithelial cells were also positive for cytokeratin 7. From the results of immunohistochemistry and histopathology, we gave the diagnosis of Mullerian choristoma with lipomyelocele.